1998
DOI: 10.1161/01.atv.18.7.1172
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of LPL Expression in Human Monocyte–Derived Macrophages Is Dependent on LDL Oxidation State

Abstract: Abstract-The regulation of macrophage lipoprotein lipase (LPL) secretion and mRNA expression by atherogenic lipoproteins is of critical relevance to foam cell formation. LPL is present in arterial lesions and constitutes a bridging ligand between lipoproteins, proteoglycans, and cell receptors, thus favoring macrophage lipoprotein uptake and lipid accumulation. We investigated the effects of native and of oxidized lipoproteins on the expression of LPL in an in vitro human monocyte-macrophage system. Exposure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 68 publications
(43 reference statements)
2
23
1
Order By: Relevance
“…These cultures have been shown previously to consist of entirely CD68ϩ macrophages (Stengel et al, 1998), and we obtained similar data in MDMs from three subjects using flow cytometry (data not shown). Media were removed from MDMs before the addition of drugs (1 ml/well), 100 nM dexamethasone (Sigma-Aldrich, St. Louis, MO), and/or 3 M SB706504 (gift from GlaxoSmithKline) previously stored in DMSO.…”
Section: Mdm Culturesupporting
confidence: 86%
See 1 more Smart Citation
“…These cultures have been shown previously to consist of entirely CD68ϩ macrophages (Stengel et al, 1998), and we obtained similar data in MDMs from three subjects using flow cytometry (data not shown). Media were removed from MDMs before the addition of drugs (1 ml/well), 100 nM dexamethasone (Sigma-Aldrich, St. Louis, MO), and/or 3 M SB706504 (gift from GlaxoSmithKline) previously stored in DMSO.…”
Section: Mdm Culturesupporting
confidence: 86%
“…Peripheral blood mononuclear cells were isolated from whole blood as described previously (Stengel et al, 1998;Kent et al, 2008). These cultures have been shown previously to consist of entirely CD68ϩ macrophages (Stengel et al, 1998), and we obtained similar data in MDMs from three subjects using flow cytometry (data not shown).…”
Section: Mdm Culturesupporting
confidence: 60%
“…In addition, adiponectin decreased the steady-state mRNA levels of class A MSR and LPL mRNA without altering those of apoE. Because class A MSR, LPL, and apoE reportedly increase during monocyte-to-macrophage differentiation, 29,31,32 adiponectin may partially modulate macrophage differentiation and affect lipid accumulation in the macrophages. The promoter assay of class A MSR revealed that adiponectin suppressed the class A MSR expression at the transcriptional level, although further studies are needed to clarify the precise transcriptional regulatory mechanism by which adiponectin decreases the class A MSR expression.…”
Section: Discussionmentioning
confidence: 94%
“…After weeks in culture, these cells grow to confluence, as described (17). The effects of immunosuppressants were also assessed in these late outgrowth EPC, human aortic endothelial cells (HAEC, Clonetics, Cambrex Bioscience) and in macrophages generated from the same initial population of PBMC (18).…”
Section: Cellsmentioning
confidence: 99%